Could different cut-off values be used for 50-gram glucose tolerance test in low and high risk groups? - Dinçgez, Burcu; Özgen, Gülten; Özgen, Levent (The European Research Journal, 2024)
Objectives: There are controversies about screening strategy and cut-off levels for gestational diabetes mellitus (GDM). Here, we aimed to identify optimal cut-off values for 50-gram oral glucose tolerance testing (OGTT) in high and low risk pregnant women. Methods: A total of 500 patients who underwent two step OGTT were divided into two groups as GDM (n=31) and controls (n=469). Moreover, patients were grouped as high (n=114) and low risk (n=386) for GDM. Having≥2 risk factors such as family history of type-2 diabetes, obesity, glucosuria, previous history of GDM, macrosomia and diabetic complications were accepted as high risk. Demographic data, OGTT results, birth characteristics were recorded and compared between groups. A cut-off value for 50-gram OGTT was evaluated in low and high risk groups. Results: The 50-gram OGTT value above 140 mg/dL discriminated GDM with 100% sensitivity and 92.11% specificity in all patients (AUC=0.969, P